Report on MSA pre congress simulator workshop 2012 - Mat Nor, Mohd Basri; Mohamed, Abdul Hadi (Malaysian Society of Anaesthesiology, 2012)
The Pre-congress workshop on simulator for 2012 Annual Scientific Meeting, Malaysian Society of Anesthesiologists/ College of Anesthesiologists was successfully organized at the Advance Clinical Skill Laboratory, IIUM, Indera Mahkota Campus, Pahang. The workshop registration was opened to all doctors and paramedics from all over Malaysia. We received participation from 24 doctors, and one of them was from Melbourne, Australia. The total of nine faculty members is from the Simulation SIG College of Anesthesiologists, Department of Anesthesiology & Critical Care, IIUM and Kandang Kerbau Hospital, Singapore. The activities included in the workshop were interactive lectures, hands-on simulation scenarios, debriefing and feedback sessions. The one-day program started at 8.00 a.m. and finished at 5 p.m. The program started with interactive lectures on ‘Crisis Management In Pediatric Patients’ by Dr. Agnes Ng SB who is a pediatric anesthetist from Kandang Kerbau Hospital, Singapore. This was followed by a second presentation on ‘Human Performance Issues – Error in Anesthesia’ by Dr. Rajeswary Kanapathipilai, a consultant pediatric anesthetist from Seremban Hospital. After the lecture, there was a short ice-breaking session to enhance interaction among the participants before the practical sessions commenced.